2011
DOI: 10.4028/www.scientific.net/amr.189-193.3026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Dry Electrostatic Cooling Assisted Machining for Hardened Steel

Abstract: Dry electrostatic cooling (DESC) assisted machining is one of the green machining technologies that uses ionized air flow as lubricating and cooling medium in the machining process. The influence of discharge parameters on the efficiency of ion transport and ozone concentration in the DESC is experimentally researched. The results show that the efficiency of ion transport increases with the rising of the discharge current and air pressure, but decreases with the rising of the distance from the nozzle and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Results obtained from the experiments showed that the ESL technology considerably reduced the tool wear and thrust force and improved the surface finish and dimensional accuracy compared with MQL and dry machining. Liu et al [13] investigated the effect of dry electrostatic cooling (DESC) technology on the cutting force and tool life in the hardened steel cutting process. The results showed that the technology utilized compressed air treated by the corona discharge could achieve better lubricating and cooling effects compared with dry cutting and consequently decreased the cutting force and tool wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained from the experiments showed that the ESL technology considerably reduced the tool wear and thrust force and improved the surface finish and dimensional accuracy compared with MQL and dry machining. Liu et al [13] investigated the effect of dry electrostatic cooling (DESC) technology on the cutting force and tool life in the hardened steel cutting process. The results showed that the technology utilized compressed air treated by the corona discharge could achieve better lubricating and cooling effects compared with dry cutting and consequently decreased the cutting force and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that electrostatic spraying could improve atomization quality and provide greater control of droplet transport, and especially could increase adsorption, penetration, and wetting rates of droplets on the targets [8][9][10]. Meanwhile, electrostatically assisted machining as a novel concept to control the cutting zone lubrication and cooling without polluting the environment has been innovated and investigated by many researches [11][12][13][14][15]. To supply constant and defined amount of cutting fluid, an electro static lubrication (ESL) technology that uses electricity instead of gas to form the fluid droplets has been developed by Reddy and Yang [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from these experiments showed the effectiveness of EL technology as a viable alternative to MQL machining. Liu et al [16] investigated the effects of dry electrostatic cooling (DEC) technology on cutting force and tool life in the hardened steel cutting process. The results showed that the technology utilizing compressed air treated by corona discharge can achieve better lubricating and cooling effects compared with dry cutting, and consequently decreases the cutting force and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…He suggested that electrostatic spray techniques can increase the adsorption and penetration rates of droplets on targets and hence reduce material consumption while minimizing waste. Meanwhile, electrostatically assisted machining as a novel method of controlling the cutting zone lubrication and cooling without polluting the environment has been investigated and improved upon by numerous researches [14][15][16]. To supply a constant and defined amount of cutting fluid, an electrostatic lubrication (EL) technology that uses electricity instead of gas to form the fluid droplets was developed by Reddy and Yang [15].…”
Section: Introductionmentioning
confidence: 99%
“…21 The multisectoral electrostatic spraying decreases the health risks and environmental pollutions, and increases the mass efficiency and bio-efficiency on to the biological surfaces with uniform deposition method. 3,16 Research work was carried out by Liu et al 22 on hardened steel under dry electrostatic cooling (DEC) condition. The impact of DEC on cutting force and tool life was assessed and it was understood based on the results that, in contrast to dry cutting, corona-based compressed air technology/method facilitates better lubrication and enhances cooling eventually leading to decrease in cutting force and tool wear.…”
Section: Introductionmentioning
confidence: 99%